Motivation for Physical Activity and Mental Health Indicators in Male Gym Attendees - Awruk Katarzyna; Janowski Konrad (Sciendo, 2016)
The significance of physical activity for mental well-being has been discussed in detail in the literature on the subject. However, a question arises concerning the relationship between motivation to exercise and psychological functioning. The objective of the present study was to test the relationship between the types of motivation for physical activity and selected indicators of mental health.